The Law on Burying Two Bodies in One Grave According to the Perspective of Islam and the Ulama - Ika Putri, Khusnul Khotimah; Dzakiyah, Dzakiyah Nur Azizah; Amalia, Ika (Fakultas Syariah Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, Indonesia, 2024)
Fardhu kifayah is the law for the people to take care of the corpse, so that if the corpse is abandoned, the Muslims around the corpse will bear the sin. The management of the corpse has rules and rights that must be fulfilled to fulfill the rights of the corpse such as: washing, shrouding, praying, and burying. The management of the corpse must be in accordance with Islamic law which is contained in the Al-Qur'an and the provisions of the Prophet. This study aims to examine the burial provisions according to Islamic law by taking into account the issue of how the law of two bodies being made into one grave according to the perspective of Islam and the scholars. Through a qualitative descriptive method with library research techniques that use books as primary and secondary sources. The results of the analysis of this study are that the law of burying two bodies in one grave is not permissible except for urgent reasons. This is in accordance with the provisions of Islamic law and the opinion of the scholars. Therefore, if there is no urgent matter such as a natural disaster, the body should be buried according to Islamic law.